2000
DOI: 10.1074/jbc.m000301200
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Production and Reactive Oxygen Species Signaling by Endothelial Nitric-oxide Synthase

Abstract: Reactive oxygen species can function as intracellular messengers, but linking these signaling events with specific enzymes has been difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 35 publications
2
56
0
1
Order By: Relevance
“…Several proteins produce O 2 Ϫ , including NAD(P)H oxidase (32), xanthine oxidase (33), NO synthase (42), and cyclooxygenase (10). The thick ascending limb expresses all of these, although NAD(P)H oxidase is likely to be a major source of O 2 Ϫ in this segment.…”
Section: No and Omentioning
confidence: 99%
“…Several proteins produce O 2 Ϫ , including NAD(P)H oxidase (32), xanthine oxidase (33), NO synthase (42), and cyclooxygenase (10). The thick ascending limb expresses all of these, although NAD(P)H oxidase is likely to be a major source of O 2 Ϫ in this segment.…”
Section: No and Omentioning
confidence: 99%
“…Importantly, eNOS is a cytochrome P450 reductase-like enzyme that produces superoxide under certain pathological conditions. 19 Vergnani et al 20 reported that oxidized LDL, an atherogenic factor, may uncouple eNOS activity, allowing the enzyme to become a source of superoxide. The interaction between NO and superoxide results in the formation of peroxynitrite, a highly toxic metabolite that can induce tissue damage, suggesting that the scavenging capacity of superoxide by endothelial SOD plays a key role in regulating the production of 2 interrelated but distinct free radicals from eNOS.…”
Section: Fukuo Et Al Nifedipine Indirectly Upregulates Endothelial Sodmentioning
confidence: 99%
“…Recently, it has become apparent that endothelial nitric oxide synthase (eNOS) can produce large amounts of superoxide under certain pathophysiological conditions. 31,32 One mechanism for this relates to oxidative destruction of tetrahydrobiopterin, which is a critical co-factor for Journal of Human Hypertension eNOS function. [33][34][35] In the absence of tetrahydrobiopterin, eNOS transfers electrons to molecular oxygen rather than to L-arginine, resulting in superoxide production.…”
Section: Receptorsmentioning
confidence: 99%